Evaluating the Cardiovascular Impact of Rheumatoid Arthritis through Clinical Disease Activity Index Scores: A Cross-sectional Study at a Rural Teaching Hospital - Saboo, Keyur; Kumar, Sunil; Acharya, Sourya; Sarode, Rajesh; Gemnani, Rinkle; Parepalli, Avinash (Journal of the Practice of Cardiovascular Sciences, 2025)
Abstract Introduction: Rheumatoid arthritis (RA) is associated with an increased risk of cardiovascular diseases, leading to higher morbidity and mortality rates compared to the general population. The Clinical Disease Activity Index (CDAI) is a validated composite index used to assess disease activity in patients with RA, which may guide therapeutic decisions and help monitor disease progression or response to treatment. This study highlights about cardiovascular evaluations at all stages of rheumatoid disease activity as per CDAI. Materials and Methods: In this prospective cross-sectional study, 55 patients aged >18 years diagnosed with RA admitted to the Medicine Department of Jawaharlal Nehru Medical College at Wardha from July 2022 to June 2024 were included in the study. The presence of left ventricular (LV) systolic, diastolic function, ejection fraction (EF), pericardial effusion, and pulmonary hypertension was confirmed by a two-dimensional echo at the time of hospital admission. Results: Out of 55 patients with RA enrolled in the study, the mean age was 53.10 ± 12.68 years having a CDAI score of more than 22. There was a significant difference between the four groups in terms of EF (P ≤ 0.001), being highest in the total CDAI score category of ≤2.8 group. There was a significant difference between the various groups in terms of LV diastolic dysfunction (LVDD, P = 0.002). Participants in the group total CDAI score category of >22 had the largest proportion of LVDD. Conclusion: We have found that most of the patients with RA had echocardiographic abnormality. The most common echocardiographic abnormality was LVDD, followed by pericardial effusion. In this study, we have highlighted about cardiovascular complications in RA as per CDAI score and published data regarding that were limited.